A Digital Comic on Lingkaran Pengider Bhuwana as the Source of Balinese Gamelan Tuning Systems - I Gusti Ayu Pitriani; I Gusti Agung Ayu Alicia Pradnya Dewi; I Wayan Swandi; A.A. Gde Bagus Udayana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Lingkaran Pengider Bhuwana, as the foundational source of Balinese gamelan tunings, embodies essential philosophical values of life balance. However, this cultural concept has become increasingly marginalized among the younger generation due to limited exposure and the lack of appealing media that introduces it in contemporary contexts. Addressing this urgency, this project presents a digital comic as an accessible and engaging medium for youth. The creative process employs the Gustami method, which involves exploring cultural phenomena and references, designing narrative and visual elements, and ultimately realizing the final digital artwork. The visual style adopts a cartoon aesthetic with dominant blue and purple tones to evoke a spiritual atmosphere, supported by the use of sacred script designs inspired by Lingkaran Pengider Bhuwana. The narrative employs a spiritual fantasy genre featuring teenage characters that symbolize the two primary Balinese gamelan tunings. This work contributes to the preservation of Balinese culture by utilizing a popular digital medium to convey cultural knowledge, encouraging young audiences to understand and appreciate the philosophical significance of Lingkaran Pengider Bhuwana.